2021
DOI: 10.3892/br.2021.1441
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases and their tissue inhibitors in the pathological mechanisms underlying maxillofacial cystic lesions

Abstract: Cystic lesions are considered to be one of the most common pathologies of the maxillofacial region, and matrix metalloproteinases (MMPs) may represent potential etiological factors. The aim of the present study was to elucidate the role of MMP-2 and MMP-9, and their endogenous tissue inhibitors, tissue inhibitor of metalloproteinase (TIMP)-1 and TIMP-2, respectively, in the pathogenesis of maxillofacial cystic lesions. A total of 25 patients diagnosed with radicular cysts (RCs; n=20), dentigerous cysts (n=3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…For instance, studies have specifically linked MMP-9 to the aggressive behavior of odontogenic keratocysts, suggesting that MMP inhibitors could serve as effective therapeutic agents. Clinical case reports have demonstrated that the local application of MMP inhibitors can significantly reduce the invasiveness of these lesions, supporting their use as adjunct therapies alongside conventional surgical methods [72,73]. This practical application highlights how understanding MMP activity can lead to more targeted and effective treatment approaches, demonstrating the direct impact of molecular insights on improving clinical outcomes.…”
Section: Matrix Metalloproteinases (Mmps) and Their Rolementioning
confidence: 83%
“…For instance, studies have specifically linked MMP-9 to the aggressive behavior of odontogenic keratocysts, suggesting that MMP inhibitors could serve as effective therapeutic agents. Clinical case reports have demonstrated that the local application of MMP inhibitors can significantly reduce the invasiveness of these lesions, supporting their use as adjunct therapies alongside conventional surgical methods [72,73]. This practical application highlights how understanding MMP activity can lead to more targeted and effective treatment approaches, demonstrating the direct impact of molecular insights on improving clinical outcomes.…”
Section: Matrix Metalloproteinases (Mmps) and Their Rolementioning
confidence: 83%
“…In a prospective investigation of 9 cystic VS, MMP-2 expression was found ubiquitously in all cyst fluid with gelatin zymography. Furthermore, MMP-2 localized to the tumors cells along the luminal surface of the cyst wall, suggesting additional roles for MMPs in the development of cysts in VS (41). Our immunofluorescence and cytokine analysis of cyst fluid did not incorporate MMPs; however, osteopontin was upregulated in cyst fluid and CSF and is known to be a substrate of several MMPs, including MMP-2 (42–45).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are divided into families depending on their internal structure and substrate. In periapical lesions, it is common to find the subfamily of collagenases (MMP-1, 8, 13) ( 113 115 ) and gelatinases (MMP-2, 9) ( 63 , 114 , 116 ), which, in combination with pro-inflammatory cytokines such as IL-1α, are involved in bone resorption during IRC growth ( 63 , 105 ). Special attention has been paid to MMP-13, which seems to have a greater implication in IRC expansion ( 33 , 63 , 113 ).…”
Section: Etiopathogenesis Of the Inflammatory Radicular Cystmentioning
confidence: 99%